Experimental system for studying long-term drought stress adaptation of wheat cultivars - Secenji, Mária; Lendvai, Ágnes; Hajósné, Zsuzsa; Dudits, Dénes; Györgyey, János (Acta Biologica Szegediensis, 2005)
Water limitation is a well-known problem for plants. Lack of water affects their biomass, their yield that is the most conspicuous in case of crops causing severe uncertainty of agricultural productivity. Under drought stress, plants generally display many physiological responses such as stomata closure, decreased/stopped photosynthetic activity, increased root/shoot ratio, reduced growth of vegetative parts. Many of the physiological changes are caused by underlying transcriptional alterations of high number of genes in many cases. One of the most studied phenomenon is the accumulation of proline as an osmoprotectant. Proline biosynthesis is increased by water deficit due to increased expression of the key enzyme, namely Δ1-pyrroline-5-carboxylate synthetase (P5CS). In our experiments, we applied P5CS as a positive control to evaluate our new experimental system, which will allow to follow transcriptional changes in shoots, as well as in roots during drought adaptation. Our alternative approach allows greenhouse or growth chamber experiments that are more similar to natural conditions than the widely used experimental systems based on osmotic agents such as polyethylene glycol (PEG).